MAKNA SIMBOLIK DALAM BL SERIES THAILAND BAGI PENGGEMARNYA - ANDRIANI, ASTRI DWI; Siti Fatimah Azzahra; Zikri Fachrul Nurhadi3; Aminah Agustinah (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
This research by Siti Fatimah Azzahra, Communication Science study program of Putra Indonesia University Cianjur, which the research title is "Symbolic Meaning in BL Series Thailand for Fans (Case Study on BL Series Thailand Fan Students at Universitas Putra Indonesia Cianjur). BL Series Thailand or Boys Love Series Thailand, is an LGBTQ+ (homosexual) drama series played by actors with attractive visuals, which is an attraction to watch BL Series Thailand. BL Series Thailand became a hit in Indonesia, after the trend of airing the series 2gether: The series on social media. In BL Series Thailand fan interactions, there are verbal and non-verbal symbolic meanings. . This is in line with the theory of symbolic interaction, which explores the meanings of each verbal and non-verbal symbol in BL Series Thailand, which is within the scope of BL Series Thailand fan interaction (Anak Raikan/Raikantopeni). This research is a qualitative descriptive research with a case study approach, data collection through interviews, participatory observation, literature studies and documentation, and data validity by trianggulation. The results of this study are: words and sentences that are familiar among BL Series Thailand fans, the most popular BL Series titles, iconic scenes in the most popular BL series, the most popular BL fandom, the most popular BL couples, gestures in the BL Series Thailand, and pictures of objects that represent certain moments of a BL Series Thailand.